2014
DOI: 10.1504/ijbaaf.2014.067021
|View full text |Cite
|
Sign up to set email alerts
|

Risk ratings and stock prices: the causal nexus in BRICS countries

Abstract: This paper investigates the nature of causal relations between risk (economic risk, financial risk and political risk) and stock prices in five BRICS countries (Brazil, Russia, India, China and South Africa), applying the Granger causality test over a period of 20 years from 1992 to 2012. The study bridges a gap in the literature, as prior macroeconomic empirical investigation has been limited to a possible link between risk ratings and stock prices. Our modelling includes BRICS stock price indices and three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…He emphasized that investors make investment decisions mostly because of the financial information of a firm. Pradhan et al (2014) find a causal relationship between economic, financial, and political risk factors and stock prices. Narayan et al (2014) observed that industrial production, which was a surrogate for economic growth and the rate of exchange (currency depreciation), had a positive impact, whereas interest rate increase had an adverse impact on stock prices.…”
Section: Introductionmentioning
confidence: 93%
“…He emphasized that investors make investment decisions mostly because of the financial information of a firm. Pradhan et al (2014) find a causal relationship between economic, financial, and political risk factors and stock prices. Narayan et al (2014) observed that industrial production, which was a surrogate for economic growth and the rate of exchange (currency depreciation), had a positive impact, whereas interest rate increase had an adverse impact on stock prices.…”
Section: Introductionmentioning
confidence: 93%